The 5th International Congress of CiiEM (IC CiiEM) 2021
DOI: 10.3390/msf2021005040
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health among Athletes at the Egas Moniz Sports Dentistry Practice

Abstract: The sports dentistry consultation at the Clínica Universitária Egas Moniz is guaranteed by a multidisciplinary team of health professionals that provide a customized service to high performance athletes. Over the last year, 99 athletes were evaluated in terms of their oral health through extraoral, intraoral and radiographic exams. In this population a high prevalence of dry mouth, erosive wear, gingivitis, periodontitis and DMF index was observed, which may have a profound and negative impact on sports perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…The results showed a significant positive influence of regular physical activity on children's salivary oxidative stress, in accordance with other studies [15,46,47]. The results of the study showed that children involved in competitive sports had significantly higher levels of GPX compared to the control group, regardless of their age group.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed a significant positive influence of regular physical activity on children's salivary oxidative stress, in accordance with other studies [15,46,47]. The results of the study showed that children involved in competitive sports had significantly higher levels of GPX compared to the control group, regardless of their age group.…”
Section: Discussionsupporting
confidence: 90%